Critical phenomena soft modes and negative Poisson’s ratio - Nemtsov, V. B.; Shirko, A. V.; Belov, V. V. (БНТУ, 2011)
The article phenomena, soft modes and negative Poisson’ ratio are considered on bases at statistical theory.